2010
DOI: 10.2139/ssrn.1578249
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Focus versus Diversification on Bank Performance: Evidence from Chinese Banks

Abstract: This paper investigates the effects of focus versus diversification on bank performance using data on Chinese banks during the 1996-2006 period. We construct a new measure, economies of diversification, and compare the results to those of the more conventional focus index, which is based on the sum of squares of shares in different products or regions. Diversification is captured in four dimensions: loans, deposits, assets, and geography. We find that all four dimensions of diversification are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 14 publications
7
95
0
3
Order By: Relevance
“…Therefore, we replace quantity of outputs in Eq. (8) with the prices of outputs, where the price of loans is measured by the ratio of interest income from loans to total loans, the price of other earning assets is measured by the ratio of interest income from other earning assets to other earning assets, and the price 6 Total cost and three outputs are divided by total assets to control for potential scale bias following Berger et al (2009Berger et al ( , 2010, Fu and Heffernan (2007), Akhigbe and McNulty (2003). 7 We add non-interest income as a proxy for non-traditional activities of banks such as loan commitment, letters of credit, bank acceptance, and services on deposit accounts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we replace quantity of outputs in Eq. (8) with the prices of outputs, where the price of loans is measured by the ratio of interest income from loans to total loans, the price of other earning assets is measured by the ratio of interest income from other earning assets to other earning assets, and the price 6 Total cost and three outputs are divided by total assets to control for potential scale bias following Berger et al (2009Berger et al ( , 2010, Fu and Heffernan (2007), Akhigbe and McNulty (2003). 7 We add non-interest income as a proxy for non-traditional activities of banks such as loan commitment, letters of credit, bank acceptance, and services on deposit accounts.…”
Section: Methodsmentioning
confidence: 99%
“…To study the first issue, we follow Berger, Hasan, and Zhou (2010) to define the economy of scope as the proportional increase in profits from producing all outputs jointly by a diversified bank compared to producing each output individually by hypothetical focused banks. More specifically,…”
Section: Profit Scope Economy and Revenue Scale Economymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the large number of studies, there appears to be no consensus on the effects of diversification on banks' economic profile (see the recent analysis by Berger et al, 2010). Some studies, however, have found evidence that financial institutions should focus on a single line of business to benefit from management expertise for different reasons: to reduce agency costs (Acharya et al, 2006;Laeven and Levine, 2007); to reduce the sources of risk (Fauver et al, 2004;Deng and Elyasiani, 2008); or to maintain profitability (Stiroh, 2004).…”
Section: Literature Review and Main Research Hypothesesmentioning
confidence: 99%